Factors That Affecting Income Persistency With Accrual Reliability As Intervening Variables Of Industrial Companies That Listed On Stock Exchange Of Thailand - Diana Dwi Astuti; Wiwik Fitrianingsih; Siti Maimunah (ABM: International Journal of Administration, Business and Management, 2020)
This study aims to analyze the factors that affect earnings persistence with accrual reliability as an intervening variable at industrial companies that listed on the Stock Exchange Thailand in 2015-2019. The data that used in this research is secondary data. The research method that reseacher used is path analysis with SPSS version 24. Based on data analysis, the conclusion of this study are there is no significant effect of the independent variables (sales volatility, cash flow volatility, good corporate governance, debt level and company size) on accrual reliability. While the independent variable that affects earnings persistence are sales volatility and company size. The results of the path analysis are the accrual reliability variable can be used as an intervening variable of cash flow volatility, good corporate governance, and debt level on earnings persistence. While sales volatility and company size, accrual realibility can not used as intervening variable to earning persistence. Keywords: Sales Volatility, Cash Flow Volatility, Good Corporate Governance, debt level, company size. Earning persistence